Bentonite-titana Composite as an Efficient, Eco-friendly and Non-toxic Catalyst for Synthesis of Benzopyran Derivatives Under Heating and Solvent-free Conditions - Darehkordi, Ali; Sadegh Hosseini, Mohammad; Mosavi, Mirrasol; Poorfreidoni, Alireza (Letters in Organic Chemistry, 2015)
Bentonite-titana composite was prepared and characterized by XRD, FT-IR and SEM. Results indicate that TiO2 particles have been supported on the bentonite layers and a delaminated structure is formed. Then the bentonitetitana composite as a mild, eco-friendly, non-toxic an efficient heterogeneous catalyst have been used for synthesis of benzopyran derivatives from the three-component condensation reaction of dimedone or barbituric acid, malonoitrile, and aromatic aldehydes under solvent free conditions in good to excellent yield and short reaction times.
Keywords: dimedone